Upregulation of FSHR and PCNA by administration of coenzyme Q10 on cyclophosphamide‐induced premature ovarian failure in a mouse model. Issue 11 (26th September 2019) - Delkhosh, Aref; Delashoub, Masoud; Tehrani, Ali Asghar; Bahrami, Ali Mohammad; Niazi, Vahid; Shoorei, Hamed; Banimohammad, Majid; Kalarestaghi, Hossein; Shokoohi, Majid; Agabalazadeh, Amin; Mohaqiq, Mahdi
Abstract: Cyclophosphamide (CTX) has been broadly used in the clinic for the treatment of autoimmune disorders and ovarian cancer. The process of chemotherapy has significant toxicity in the reproductive system as it has detrimental effects on folliculogenesis, which leads to an irreversible premature ovarian failure (POF). Coenzyme Q10 (CoQ10) has positive impacts on the reproductive system due to its antioxidant properties, protecting the cells from free‐radical oxidative damage and apoptosis. However, little is known about the possible synergistic effect of CTX and CoQ10 on the expression of genes involved in folliculogenesis, such as proliferation cell nuclear antigen (PCNA) and follicle‐stimulating hormone receptor (FSHR). A total of 32 NMRI mice were applied and divided into four groups, including healthy control, CTX, CTX + CoQ10, and CoQ10 groups. The effects of CoQ10 on CTX‐induced ovarian injury and folliculogenesis were examined by histopathological and real‐time quantitative reverse transcription‐polymerase chain reaction analyses. The rates of fertilization (in vitro fertilization), embryo development, as well as the level of reactive oxygen species (ROS) in metaphase II (MII) mouse oocytes after PMSG/HCC treatment were also assessed. Results showed that the treatment with CTX decreased the mRNA expression of PCNA and FSHR, IVF rate, and embryo development whereas the application of CoQ10 successfully reversed those factors. CoQ10 administration significantly enhanced histological morphology and decreased ROS levels and the number of atretic follicles in the ovary of CTX‐treated mice. In conclusion, it seems that the protective effect of CoQ10 is exerted via the antioxidant and proliferative properties of this substance on CTX‐induced ovarian damage.